PENGARUH KARAKTERISTIK PERUSAHAAN DAN KUALITAS AUDITOR TERHADAP KUALITAS LAPORAN KEUANGAN - Fernanda Gusti Cahyani (2023)
This research is a quantitative research conducted with the aim of examining the effect of firm characteristics as represented by liquidity, leverage, profitability, firm size, and firm age and auditor quality on the quality of financial statements. This study uses secondary data from transportation and logistiks sector companies listed on the Indonesia Stock Exchange (IDX) in the 2018-2021 period. Sampling used a purposive sampling method which produced a total of 60 samples. Testing the hypothesis in this study uses a multiple linear regression model assisted by Microsoft Excel 2016 and STATA Version 17 software. The results of this study are: (1) Liquidity has no effect on quality of financial reports (2) Leverage has no effect on quality of financial reports (3) Profitability has no effect on quality of financial statements (4) Firm size has no effect on quality of financial statements (5) Firm age has no effect on quality of financial statements (6) Auditor quality has no effect on quality of financial statements.